Robinh

02-07-2008, 03:00 AM

Hi.

Love the book!

Section 6.11 talks about inverting the function

y = x*log(x).

It doesn't mention the Lambert W function, which inverts

y = x*exp(x). Thus W(x)*exp(W(x)) = x.

The y(x) of equation 6.11.1 would then be exp(W(x)).

There are a load of references (the canonical one would be

Corless 1996).

HTH, Robinh

Love the book!

Section 6.11 talks about inverting the function

y = x*log(x).

It doesn't mention the Lambert W function, which inverts

y = x*exp(x). Thus W(x)*exp(W(x)) = x.

The y(x) of equation 6.11.1 would then be exp(W(x)).

There are a load of references (the canonical one would be

Corless 1996).

HTH, Robinh